(untitled) (Annals of Medical Research, 2021)
Aim: Elevated preoperative neutrophil–lymphocyte ratio (NLR) and platelet–lymphocyte ratio (PLR) predict overall survival rates among patients with several types of cancer. The current study was conducted to clarify whether NLR and PLR are clinically useful in predicting overall survival among patients undergoing curative resections for gastric cancer. Material and Methods: 202 gastric cancer patients were reviewed retrospectively who had been appealed to our clinic between 2006 and 2013. 192 patients who had local disease, and underwent curative surgery for gastric cancer were included to the study. Data regarding potential prognostic factors including age, sex, preoperative neutrophil, lymphocyte, and platelet counts, postoperative tumor characteristic such as tumor location, tumor size, lymph node metastasis, tumor–nodes–metastasis staging, Lauren’s classification of subtypes and survival times were obtained from medical records.Results: No significant correlations were noted between NLR, PLR and tumor location, size, Lauren’s classification of subtypes, histology, stage, and type of gastrectomy. Univariate analysis revealed that metastasis at the follow up, sex, T, N stage, and lymph node ratio (LNR) were predictors of worse overall survival. In multivariate analysis, metastasis at follow up (p=0.014; HR:1.81; CI:1,126-2,911) and LNR (p=0.001; HR:3,564; CI:2,175-5,842) were found to be independent variables with worse overall survival. Conclusion: Preoperative NLR and PLR cannot be used as independent variables for prediction of overall survival in patients with operable gastric cancer.